NEW FIR LASER LINES AND FREQUENCY MEASUREMENTS FROM OPTICALLY PUMPED CD-13(3)OH-3 - Moraes, João Carlos Silos [UNESP]; Telles, E. M.; Cruz, F. C.; Scalabrin, A.; Pereira, D.; Garelli, C.; Ioli, N.; Moretti, A.; Strumia, F. (Plenum Publ Corp, 1991)
We report the discovery of 57 new fir laser lines from (CD3OH)-C-13 molecule optically pumped by a waveguide CO2 laser of 300 MHz tunability. For all lines, precise frequency offset measurements between the CO2 line center and the center of the absorbing (CD3OH)-C-13 line were performed using the transferred Lamb-Dip technique. We have also measured directly the frequency of seven FIR laser lines by heterodyning with already known laser lines.We present a complete list of all known laser lines (134) and frequency measurements (24) for this molecule.